Coupling an urban parameterization to an atmospheric model using an operational configuration - Nobis, Timothy E., author; Pielke, Roger A., advisor; Collett, Jeffrey L., committee member; Johnson, Richard H. (Richard Harlan), committee member; Meroney, Robert N., committee member (Colorado State University. Libraries, 2010)
Operational weather centers use numerical weather prediction (NWP) models to provide forecast weather guidance. Output from these models are then used to drive non-weather decision aids such as air quality forecast or dispersion models which are sensitive to near surface weather and very important in urban areas. While NWP models are usually run at resolutions fine enough to allow them to account for mesoscale flow systems (e.g. sea breeze), they are not designed to explicitly model an urban heat island (UHI) response. Other studies have shown that the UHI can interact with and alter local mesoscale flow systems in and around urban areas. This study examines the ability of an urban parameterization to improve operational NWP characterization of the sensible weather in Washington, DC on three separate days. The urban parameterization does seemly function in a subjective fashion to create many of the typical UHI features in spite of being run at a much coarser resolution than typically used with urban parameterization studies. When compared to actual near surface temperature data, while the parameterization was found to significantly underestimate the strength of the UHI (likely a product of the resolution), it does act to reduce the forecast temperature error in the District, especially when compared against an available vertical temperature profile. The parameterization did perform more ambiguously in the transition area between the suburban and rural regions where it seems the resolution was not high enough to model the often observed sharp transition between urban and rural environment. Overall, the presence of an urban parameterization seemed to improve the model's characterization of the near surface environment around Washington, DC.
Keywords: town energy balance model; numerical weather prediction; urban heat island; urban parameterization; Washington, DC; Urban heat island -- Models -- Washington (D.C.); Weather forecasting -- Models -- Washington (D.C.); Atmospheric temperature -- Washington (D.C.) -- Forecasting